Religion And Social Culture of the People of West Kalimantan’s Penata Island - D. Darmadi JA (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
The Penata Island, also called the Fishermen’s Contact Village, exemplifies the Indonesian people’s characters in general. These characters are preserved to this day in the village to reflect social behavior of the people as native culture of Indonesia, such as helping each other, a sense of community life, and work discipline. When they have problem, they are able to resolve it wisely through community leaders. When the problem is not resolved, it will be taken to the police and resolved through other legal ways. From the results of this study, the researcher saw a few things that have not been done properly, for example, the fishermen have yet to perform the five-time prayers. Some of them are involved in gambling and liquor-drinking, though it is a restricted case that does not have any influence on behavior patterns of the community members in general especially with regard to the practice of Islamic religious teachings.